(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
The article analyzes the growing season of the ridges created by the authors, mainly the indicators “germination-50% flowering” and“germination-50% ripening”. As a result of studies, t-340 and T-160 ridges have been isolated in frequency, and they have been recommended for future use in genetic-selective research.